Motivacijski profili odraslih v formalnem izobraževanju - Radovan, Marko (AS. Andragoška spoznanja, 2008)
The article describes the international project "Participation of the adults in the formal education system", which studies characterisstics of formal education with the influences on viewpoints, motives and motivations for education. Apart from the theoretical bases of the project, motives encouraging individuals to register for formal education programmes are introduced.
Keywords: izobraževanje odraslih; andragogika; Andragogy; formalno izobraževanje; motivacija; motivation; projekti; mednarodne raziskave